The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1128/aac.00947-19
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Nevirapine on Artemether-Lumefantrine Pharmacokinetics in Individuals Stratified by CYP2B6 c.516G>T Genotypes

Abstract: There is an increased recognition of the need to identify and quantify the impact of genetic polymorphisms on drug-drug interactions. This study investigated the pharmacogenetics of the pharmacokinetic drug-drug interaction between nevirapine and artemether-lumefantrine in HIV-positive and HIV-negative adult Nigerian subjects. Thirty each of HIV-infected patients on nevirapine-based antiretroviral therapy and HIV-negative volunteers without clinical malaria, but with predetermined CYP2B6 c.516GG and TT genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Another study amongst Nigerian HIV-malaria infected subjects explored the impact of CYP2B6 516GT polymorphism on NVR and artemether-lumefantrine drug-drug interaction. The authors showed that decreased exposure to artemether and desbutyl-lumefantrine caused by NVR was further enhanced by patients with CYP2B6 516GG genotype (ultrarapid metabolizers) (Abdullahi et al, 2020 ). Again, the CYP2B6 516TT genotype (poor metabolizers) also influenced increased exposure to dihydroartemisinin and lumefantrine caused by NVR (Abdullahi et al, 2020 ).…”
Section: Population Disparity In the Use Of Cyp2b6 Substrates And Consequent Exposure To Substrate-specific Adverse Drug Reaction (Adr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Another study amongst Nigerian HIV-malaria infected subjects explored the impact of CYP2B6 516GT polymorphism on NVR and artemether-lumefantrine drug-drug interaction. The authors showed that decreased exposure to artemether and desbutyl-lumefantrine caused by NVR was further enhanced by patients with CYP2B6 516GG genotype (ultrarapid metabolizers) (Abdullahi et al, 2020 ). Again, the CYP2B6 516TT genotype (poor metabolizers) also influenced increased exposure to dihydroartemisinin and lumefantrine caused by NVR (Abdullahi et al, 2020 ).…”
Section: Population Disparity In the Use Of Cyp2b6 Substrates And Consequent Exposure To Substrate-specific Adverse Drug Reaction (Adr)mentioning
confidence: 99%
“…The authors showed that decreased exposure to artemether and desbutyl-lumefantrine caused by NVR was further enhanced by patients with CYP2B6 516GG genotype (ultrarapid metabolizers) (Abdullahi et al, 2020 ). Again, the CYP2B6 516TT genotype (poor metabolizers) also influenced increased exposure to dihydroartemisinin and lumefantrine caused by NVR (Abdullahi et al, 2020 ). According to the authors, the inductive effect of NRV on CYP2B6 and CYP3A4 enzymes, both of which are involved in the metabolism of these antimalarial drugs, might have caused this variability (Abdullahi et al, 2020 ).…”
Section: Population Disparity In the Use Of Cyp2b6 Substrates And Consequent Exposure To Substrate-specific Adverse Drug Reaction (Adr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, selecting regimen combinations based upon known underlying favourable enzymatic profiles able to compensate in the opposite direction potential unfavourable enzymatic induction/inhibition of DDIs may preserve treatment options, outcomes, and adherence by reducing concentrations below/above the therapeutic range. In this regard, recent data showed a differential impact of the co-administration of nevirapine and antimalarial regimens when stratified by CYP2B6 polymorphisms [ 49 ]: the nevirapine-induced reduction of artemether and desbutyl-lumefantrine and increase of dihydroartemisinin and lumefantrine significantly differed between CYP2B6 c516GG versus TT genotypes [ 49 ]. If geographical PG data were easily and widely available, population-physiologically-based PK modelling could classify the same co-administration as contraindicated in some areas while recommended or neutral in others.…”
Section: Malaria and Hivmentioning
confidence: 99%
“…CYP2B6 gene is located in 19q12–13.2, with a total length of 27.1 kb, including 11 exons which encode 491 amino acids [22] . A number of variants have been found in CYP2B6 such as NM_000767.5:c.516G>T ( CYP2B6 c.516G>T) variant which affects the activity of CYP2B6, and reduces the rate of human transformation of carcinogenic substances into inactive metabolites, which leads to the accumulation of carcinogenic substances, and a series of diseases [23–26] …”
Section: Introductionmentioning
confidence: 99%